HARMONISASI HUKUM PERIKANAN UNTUK KESEJAHTERAAN KELAUTAN INDONESIA - Emiel Salim Siregar; Celly Naomi Sarah Br Napitupulu; Lica Adilla; Nurul Akmal; Muhammad Idham (Universitas Wiralodra, 2025)
The rapid growth of the fisheries industry in Indonesia highlights the urgent need to formulate and implement legal policies that are in line with sustainability principles. This abstract discusses efforts to